2014
DOI: 10.1172/jci70391
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclin-dependent kinase inhibitor 2B regulates efferocytosis and atherosclerosis

Abstract: Genetic variation at the chromosome 9p21 risk locus promotes cardiovascular disease; however, it is unclear how or which proteins encoded at this locus contribute to disease. We have previously demonstrated that loss of one candidate gene at this locus, cyclin-dependent kinase inhibitor 2B (Cdkn2b), in mice promotes vascular SMC apoptosis and aneurysm progression. Here, we investigated the role of Cdnk2b in atherogenesis and found that in a mouse model of atherosclerosis, deletion of Cdnk2b promoted advanced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
136
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 82 publications
4
136
0
1
Order By: Relevance
“…5 Although it is tempting to conceptualize the VSMC as existing in only 1 of 2 dichotomous states (ie, either a synthetic or contractile state), it is important to note that these changes occur on a spectrum and that in addition to re-entering the cell-cycle, the dedifferentiated VSMC can also activate programmed cell death pathways 6,7 and elaborate proinflammatory cytokines. 8 Furthermore, the activated VSMC can go to date as to assume behaviors typically ascribed only to other cell types, including phagocytosis and efferocytosis, 9 ossification, 10 reverse cholesterol transport, 9,11 and even foam cell formation. 12,13 Indeed, one of the more exciting recent findings made possible by the use of elegant in vivo lineage tracing systems suggests that the VSMC can assume a macrophagelike phenotype in the developing atherosclerotic plaque, thus challenging the paradigm that lesional foam cells arise predominantly from bone marrow-derived monocytes.…”
Section: Pathophysiology Of the Vsmcmentioning
confidence: 99%
“…5 Although it is tempting to conceptualize the VSMC as existing in only 1 of 2 dichotomous states (ie, either a synthetic or contractile state), it is important to note that these changes occur on a spectrum and that in addition to re-entering the cell-cycle, the dedifferentiated VSMC can also activate programmed cell death pathways 6,7 and elaborate proinflammatory cytokines. 8 Furthermore, the activated VSMC can go to date as to assume behaviors typically ascribed only to other cell types, including phagocytosis and efferocytosis, 9 ossification, 10 reverse cholesterol transport, 9,11 and even foam cell formation. 12,13 Indeed, one of the more exciting recent findings made possible by the use of elegant in vivo lineage tracing systems suggests that the VSMC can assume a macrophagelike phenotype in the developing atherosclerotic plaque, thus challenging the paradigm that lesional foam cells arise predominantly from bone marrow-derived monocytes.…”
Section: Pathophysiology Of the Vsmcmentioning
confidence: 99%
“…The same authors then went on to show that Cdnk2b-deficient mice developed increased atherosclerosis with advanced plaques and large necrotic cores accompanied by impaired efferocytosis of apoptotic bodies by macrophages, increased foam cell formation, and increased inflammatory responses. 4 Although much work remains to be done, these findings implicate CDKN2B as potentially causally involved vascular diseases associated with genetic variation at C9CAR, suggesting that regulation of vascular smooth muscle cell apoptosis may be an important mediator, and also implicate the potential for p53 involvement in vascular disease.…”
Section: Chromosome 9p213 Coronary Heart Disease-associated Regionmentioning
confidence: 99%
“…CDKN2B has been previously detected as a candidate gene in CHD (19)(20)(21). Kojima et al (22) demonstrated that loss of CDKN2B promoted advanced development of atherosclerotic plaques, which suggests a crucial role for CDKN2B in the initiation and development of CHD. An inverse correlation between CDKN2B hypermethylation and low expression has previously been found in CHD (23).…”
Section: Introductionmentioning
confidence: 99%